2016
DOI: 10.23937/2469-5734/1510033
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Related Osteonecrosis of the Jaw with the mTOR Inhibitor Everolimus in a Patient with Estrogen-Receptor Positive Breast Cancer: A Case Report

Abstract: with breast cancer under the age of 50-years (approximately 49,000 women) and is a leading cause of death in this age group [1]. It is estimated that over 40,000 women will die of this disease in 2015 [2]. More than 50% have estrogen-receptor positive (ER+) disease, although estrogen is a steroid sex hormone required for normal breast development [3]. There is a strong correlation between exposure to estrogen and development of breast cancer [3,4]. Breast cancer due to elevated blood levels of estrogen is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…It is known, for example, that the combination of anti-VEGFR and bone antiresorptive agents may increase the risk of MRONJ [ 60 , 61 , 62 ]. Similarly, it was well confirmed that mTOR inhibitors have a strong immunosuppressive effect, which can lead to delayed healing of oral soft tissues and persistent infections favoring the onset of the osteonecrotic process [ 63 , 64 ]. Taking into account these observations and their potential etiologies, the following hypothesis has been developed for MRONJ onset: (1) a direct local effect represented by the epithelial damage [ 65 , 66 , 67 , 68 , 69 ]; (2) an indirect systemic effect exerted by the immunosuppressive action of anti-cancer treatments [ 70 , 71 ], since the new concept of osteoimmunology [ 72 ] was recently added to the previous etiopathogenetic theories on MRONJ development [ 73 ]; and lastly, (3) the hypothesis that new anticancer drugs may play a role in osteoclast differentiation by additionally affecting the RANKL-mediated cell cycle arrest, as supported by recent in vitro and in vivo data [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known, for example, that the combination of anti-VEGFR and bone antiresorptive agents may increase the risk of MRONJ [ 60 , 61 , 62 ]. Similarly, it was well confirmed that mTOR inhibitors have a strong immunosuppressive effect, which can lead to delayed healing of oral soft tissues and persistent infections favoring the onset of the osteonecrotic process [ 63 , 64 ]. Taking into account these observations and their potential etiologies, the following hypothesis has been developed for MRONJ onset: (1) a direct local effect represented by the epithelial damage [ 65 , 66 , 67 , 68 , 69 ]; (2) an indirect systemic effect exerted by the immunosuppressive action of anti-cancer treatments [ 70 , 71 ], since the new concept of osteoimmunology [ 72 ] was recently added to the previous etiopathogenetic theories on MRONJ development [ 73 ]; and lastly, (3) the hypothesis that new anticancer drugs may play a role in osteoclast differentiation by additionally affecting the RANKL-mediated cell cycle arrest, as supported by recent in vitro and in vivo data [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%